A Semiotic Analysis of Roland Barthes on MS Glow Beauty Advertisement on YouTube - Siahaan, Rut Damai Yanti (TRANSFORM: Journal of English Language Teaching and Learning, 2025)
This study is about analyzing semiotic of Roland Barthes on MS Glow Beauty Advertisement on YouTube. The objectives of this study were to find out the denotative and connotative meaning also the myths’ representation used by MS Glow throughout the classification of signifier and signified. The method used in this study was descriptive qualitative method. The data was about 16 screenshots captured consists of visual and verbal signs which taken from the 3 sources data that is contained in MS Glow Beauty advertisement on YouTube. The findings showed a number of visual signs and verbal signs had balanced where visual signs for picture had 14 signs and visual signs for text in picture had 13 signs, while the verbal signs with tag line consists 11 signs and verbal signs with dialogue consists 16 signs. Both of visual signs and verbal signs conveyed denotative meaning that is realized by visual signs as picture or text in picture, verbal signs as tag line or dialogue. Meanwhile, connotative meaning realized as giving meaning for every single sign and the myths’ representation for advertisements where belief of beauty was belongings to women who have white skin only, not for dark skin and it was also occurred for men. The implication of this study is to give understanding of semiotic approach focused on advertisement.